Increasing the international role of the euro: A long way to go - Marek Dabrowski (Center for Social and Economic Research (CASE), 2020)
The euro is the second most important global currency after the US dollar. However, its international role has not increased since its inception in 1999. The private sector prefers using the US dollar rather than the euro because the financial market for US dollar-denominated assets is larger and deeper; network externalities and inertia also play a role. Increasing the attractiveness of the euro outside the euro area requires, among others, a proactive role for the European Central Bank and completing the Banking Union and Capital Market Union.
Keywords: E42; E58; F33; 330; global currency; dominant currency; euro; US dollar; international monetary system; European Union; euro area; network externalities; power of incumbency